Effects of Hormonal Changes During Puberty on Cognition and Mood - Li, Yige (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This article explores the hormone surge during puberty and its wide-ranging effects on adolescent behavior, mood, and cognition, highlighting the importance of this area for future research. The onset of puberty leads to increased secretion of sex hormones such as estrogen and testosterone, which bring physical, emotional, and behavioral changes by activating the hypothalamic-pituitary-gonadal axis. This article provides insights into how these hormones affect adolescent brain development, particularly areas such as the prefrontal cortex and hippocampus that are responsible for higher-order thinking and memory. Hormone fluctuations not only affect adolescents’ attention and processing abilities, but also lead to mood swings, increased stress sensitivity, and sex differences in externalizing behaviors (such as aggression) and emotion regulation. Girls are more prone to mood swings due to cyclical fluctuations in estrogen and progesterone, while boys exhibit risk-taking behaviors associated with testosterone. In addition, sex hormones affect adolescents’ social cognition, self-esteem, and body image, leading to increased insecurity and social sensitivity. This article calls for providing adolescents with healthy coping strategies and supportive environments, and, if necessary, therapeutic interventions to help them through the challenges of this period, and points to directions for future research.